Effect of Natural Antioxidants from Fruit Leaves on the Oxidative Stability of Soybean Oil during Accelerated Storage - Hanem M. M. Mansour; Sobhy Ahmed El-Sohaimy; Ahmed M. Zeitoun; Eman M. Abdo (MDPI AG, 2022)
Plant by-products are safe, sustainable, and abundant natural antioxidant sources. Here we investigated the antioxidant activity of a mixture of lyophilized pomegranate, guava, and grape (PGG) leaves water extract (1:1:1) and examined its ability to retard the rancidity of soybean oil during accelerated storage at 65 °C for 30 days. To achieve this, we evaluated the oxidative stability of soybean oil enriched with PGG extract at 200, 400, and 800 ppm. We also compared the effect of PGG extract with butylated hydroxytoluene (BHT) (400/100 ppm) with that of only BHT (200 ppm). We observed that 8.19 and 1.78 µg/mL of the extract could scavenge 50% of DPPH• and ABTS•, respectively, indicating its enhanced antioxidant activity. Enriching soyabean oil with the extract at 800 ppm improved its oxidative stability by reducing the acid value to 1.71 mg/g and the total oxidation to 99.87 compared to 2.27 mg/g and 150.32 in the raw oil, respectively. Moreover, PGG-800 ppm inhibited oxidation by 46.07%. Similarly, PGG-400 ppm reinforced BHT (100 ppm) to provide oxidative stability as BHT (p > 0.05), with TOTOX values of 87.93 and 79.23, respectively. PGG-800 ppm and PGG/BHT mix potently inhibited the transformation of polyunsaturated fatty acids into saturated ones. Therefore, the PGG extract might be an efficient substitute for BHT (partially or totally) during industrial processes.